„Il vento del Baltico”: dagli scioperi di Danzica al riconoscimento di Solidarność, la Polonia del Corriere della Sera (luglio–agosto 1980) - B e l l i f e m i n e, Onofrio (Colloquia Litteraria, 2023)
This work describes how Corriere della Sera reported the great workers’ strikes in Gdansk (August 1980). The Polish events immediately attracted the attention of the Italian press also due to the important role played by Pope John Paul II. Corriere della Sera, one of the oldest and most important Italian newspapers is the point of reference for the moderate liberal bourgeoisie. Thanks to the work of reporters and intellectuals such as vittorio Zucconi, Sandro Scabello, Leo valiani, enzo Biagi, Alberto ronchey has recounted these events in an absolutely interesting and original way.